Toxicological Evaluation of Ashtabhairava mathirai Acute and Subacute Safety Assessment - Marimuthu, Raghavi; Balasubramani, Abarna; Ramamoorthy, Karpagambal; Ramasamy, Suresh; Rajaraman, Rajasri; Rajathinakaran, Sathish Adithya; Ramachandran, Madhavan (Asian Journal of Biological and Life Sciences, 2025)
Background/Purpose: Ashtabhairava mathirai (ABM), a traditional Siddha formulation referenced in the Siddha Vaidhiya Thirattu, is traditionally used to treat 64 types of fever. Despite its historical significance, scientific validation of its safety is crucial for its acceptance in modern medicine. This study aimed to evaluate the acute and subacute toxicity of ABM using Wistar albino rats (Rattus norvegicus). Materials and Methods: Wistar albino rats were used for acute (OECD 423) and subacute (OECD 407) toxicity studies. Behavioral, biochemical, and histopathological parameters were analyzed. Data were statistically evaluated using one-way ANOVA (p<0.05). Results: The findings of the study demonstrated that all evaluated parameters remained within normal limits, with no mortality observed throughout the experimental period. The acute oral toxicity assessment indicated that the LD50 value of Ashtabhairava mathirai (ABM) exceeds 2000 mg/kg body weight. Additionally, the repeated dose 28-day oral toxicity study determined No Observed Adverse Effect Level (NOAEL) of more than 150 mg/kg body weight. Histopathological examinations of vital organs provided further reassurance, as no abnormalities or adverse changes were noted, supporting safety of the formulation. Conclusion: These results confirm the safety of ABM for further clinical investigations but also validate its ongoing use in traditional practices. This study offers a thorough preclinical safety evaluation of ABM, providing scientific support for its traditional applications and potential as a therapeutic agent in future medical use.
Keywords: Acute toxicity; Ashtabhairava mathirai; Fever; OECD; Repeated dose 28-day oral toxicity study; Siddha; Toxicity study